The effects of online interruption pace and richness on task performance. - Levy, Eliat Chen; Rafaeli, Sheizaf; Ariel, Yaron (Atlantic Journal of Communication)
This study investigates the impact of online interruption pace and information richness on managerial task performance. A computer game simulating external interruptions online was used to expose participants to either a slow or rapid pace of interruptions and provide them with either lean or rich information during the task. Task performance was measured based on the points scored in the game. Results indicate that the pace of interruptions significantly affected task performance, with participants experiencing a slow pace of interruptions performing better than those experiencing a rapid one. Information richness did not significantly affect task performance. However, the interaction between the two variables significantly affected task performance, with optimal performance occurring with fewer interruptions and richer information. The growing prevalence of remote work and its potential for more frequent and varied interruptions calls for investigating a more complex model of interruption effects, helping managers better understand interruptions in work environments.